DSpace-Dev @ University of Minho: development of tools and add-ons for the DSpace platform - Ferreira, Miguel (2005)
DSpace related activities at University of Minho (UM) started in April 2003 and since then many developments have been made. The first step was taken by the University Documentation Services (SDUM) with the translation of DSpace to Portuguese which was followed by the implementation of the RepositóriUM, the university’s institutional repository. The translated version of DSpace has been downloaded and used in many other institutions in Portugal and Brazil. This very same version of DSpace served as a basis for the Papadocs system – a system which aimed at providing access to all assignments developed by the students of the Department of Information Systems. This instance of DSpace also served as test bed for a series of add-ons created at the department, namely, the Commenting Add-on, the Recommendation Add-on, the Web of Communication Add-on and the Controlled Vocabulary Add-on. This project has lead to the formation of several interesting ideas. These include the improvement of the Controlled Vocabulary Add-on to support more complex structures, such as thesauri, and the development of automatic metadata extractors that could fill in some of the required metadata during the process depositing new items.